The Influence of Excessive Workload and Work Stress towards the Auditor’s Turnover Intention with Job Satisfaction as Mediation Variable - Christyandita Wulansari; Bambang Subroto; Endang Mardiati (Jurnal Ilmiah Akuntansi, 2021)
The present study is a statistical hypothesis test aimed at investigating the influence of the independent variables such as excessive workload and work stress toward the dependent variables such as job satisfaction and the auditor's intention of a junior auditor who worked at Public Accountant Firm with a “Big Four” status. The research population was the auditors of the Public Accountant Firm in the category of” Big Four” whereas, in Indonesia means in 6 months to 2 years of service. The method used was a survey method with primer data through a questionnaire which was processed using SmartPLS 3.0. The result of this research proofed that excessive workload influences turnover intention. Meanwhile, work stress influences both job satisfaction and turnover intention. The research also showed excessive workload does not influence job satisfaction, and job satisfaction does not influence turnover intention.